Effect of Soil Type and Foliar Factors on the Distribution of Imbrasia belina in the Southeastern Lowveld of Zimbabwe - Mufandaedza, Edward; Moyo, Doreen Z.; Makoni, Paul (Hindawi Limited, 2021)
The aims of this study were to find out whether soil parameters (i.e., soil texture, soil pH, and available nitrogen (N) and phosphorus (P)) and level of tannins in the bark of tree as measured by total amount of N & P in the droppings significantly influenced Imbrasia belina distribution in the Southeastern Lowveld of Zimbabwe. The samples were collected in February-March 2013. Standard methods were employed on 80 samples across the four tenure regimes studied. Soil pH, percentage clay, silt, and sand were randomly measured across the four tenure regimes. The study results revealed that soil pH (), % silt (), % sand (), available nitrogen (), available phosphorus (), and the mean tannin level () influenced the distribution of Imbrasia belina in the study area. Multiple comparison analysis showed that there were significant differences in percentage clay () between Gonakudzingwa Small-Scale Farms (GSSCF) and Chikombedzi Communal Area (CCA). However, Mwenezi Resettlement Area (MRA) and Gonarezhou National Park (GNP) results were insignificant for percentage silt () and percentage sand (), respectively. The soil and foliar factors discussed are critical in determining Imbrasia belina distribution, forest health, and vitality.